The transmembrane adaptor protein NTAL signals to mast cell cytoskeleton via the small GTPase Rho - Tůmová, Magda; Koffer, Anna; Simíček, Michal; Dráberová, Lubica; Dráber, Petr (European journal of immunology, 2010)
The transmembrane adaptor protein NTAL (non-T-cell activation linker) participates in signalosome assembly in hematopoietic cells, but its exact role in cell physiology remains enigmatic. We report here that BM-derived mast cells from NTAL-deficient mice, responding to Ag alone or in combination with SCF, exhibit reduced spreading on fibronectin, enhanced filamentous actin depolymerization and enhanced migration towards Ag relative to WT cells. No such differences between WT and NTAL(-/-) BM-derived mast cells were observed when SCF alone was used as activator. We have examined the activities of two small GTPases, Rac and Rho, which are important regulators of actin polymerization. Stimulation with Ag and/or SCF enhanced activity of Rac(1,2,3) in both NTAL(-/-) and WT cells. In contrast, RhoA activity decreased and this trend was much faster and more extensive in NTAL(-/-) cells, indicating a positive regulatory role of NTAL in the recovery of RhoA activity. After restoring NTAL into NTAL(-/-) cells, both spreading and actin responses were rescued. This is the first report of a crucial role of NTAL in signaling, via RhoA, to mast cell cytoskeleton.
Keywords: rac proteiny vázající GTP; myši; antigeny; aktiny; signální transdukce; adaptorové proteiny signální transdukční; Mice, Knockout; myši knockoutované; mastocyty; Signal Transduction; Proteins; Antigens; Mast Cells; rac GTP-Binding Proteins; buňky kostní dřeně; proteiny; Mice; Animals; rho GTP-Binding Proteins; zvířata; cytoskelet; Rho proteiny vázající GTP; Bone Marrow Cells; Actins; rhoA protein vázající GTP; rhoA GTP-Binding Protein; Adaptor Proteins, Signal Transducing; Cytoskeleton